Challenges in inpatient care coordinators' clinical workflow and opportunities in designing a health IT solution: A mixed methods study. (June 2022) - Wu, Danny TY; Murdock, Paul; Vennemeyer, Scott; Mynatt, Janie M; Chih, Ming-Yuan
Introduction: Inpatient care coordinators (ICCs) in the United States play a critical role in case management and care transition. ICCs spend a large amount of time in chart review and documentation through electronic health record (EHR) systems. However, significant knowledge gaps exist regarding their workflow barriers and their use of health information technology (Health IT). Using only quantitative or quantitative methods does not provide a comprehensive picture about ICC's workflow due to its complex and dynamic nature. This work aimed to address this gap by conducting a mixed-methods study to understand the workflow of ICCs and identifying challenges in care deliver and documentation activities. Methods: The study adopted a concurrent triangulation design including qualitative interviews with 12 ICC staff members in the United States followed by extraction of their EHR event logs for one month. The qualitative interview data were analyzed thematically, and the log data were analyzed statistically. The results were triangulated and interpreted. Results: Three major workflow barriers faced by ICCs were identified: long travel time, heavy documentation load, and suboptimal communication. The event logs provided empirical evidence to support the workflow barriers identified in the interviews, especially in travel time and documentation load. Discussion: ICC workflow has several inefficiencies. The study generated four design considerations to develop a Health IT solution: Mobility, EHR integration, Team-based Communication, and User Adoption to improve workflow efficiency and care coordination. Using a mixed-methods approach is effective and efficient in collecting and analyzing clinical workflow.